Acceptability of Subtitle on "Charlie and the Chocolate Factory" Film - Ade Putri Setyo Wardhani; Pradita Dwi Ayu Wulansari; Ajeng Noer Olivia; Fitry Alfarisy (2022)
This study aims to determine how acceptable a subtitle is for a film with a PG-Rating. This study was conducted using a descriptive qualitative research approach. The object of this study is a popular film, watched by children. The human instrument is used as a research instrument; the researchers determine study focus, data sources, obtain data, analyze data, interprets data, and draws conclusions. The data is from the subtitle of the film 'Charlie and the Chocolate Factory' on 'Netflix.' The note-taking approach is used to collect the data from subtitle texts, ensuring that the data is correct. The data includes subtitle timing, characters, source language, and target language. The data is analyzed based on the measurement of a translation's level of acceptability. This study findings show that some translations in the film 'Charlie and the Chocolate Factory' are still unacceptable and less acceptable for a PG-Rating film with child audiences.